1992
DOI: 10.1172/jci115837
|View full text |Cite
|
Sign up to set email alerts
|

Predominant activation and expansion of V gamma 9-bearing gamma delta T cells in vivo as well as in vitro in Salmonella infection.

Abstract: Abstract'yb T cell receptor-positive cells ('yb T cells) 'yb T cell activation was significantly higher than a13 T cell activation at the early stage ofillness (P < 0.01 ). When peripheral blood lymphocytes from normal individuals were cultured with live salmonella, 'y T cells were preferentially activated and expanded and most of them expressed Vy 9. Purified 'yS T cells also responded to live salmonella in vitro. The present study suggests that human ' T cells play a role in the protection against salmonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 48 publications
4
95
0
Order By: Relevance
“…Specifically, we found that γδ T cells were subtly activated, or primed, early in Salmonella serovar Typhimurium-infected calves, as evidenced by the increase in IL-2Rα on cells derived from intestinal lymphatic ducts. Minimal changes in γδ T cells were observed in the blood of infected calves, consistent with responses seen in human Salmonella serovar Typhimurium induced enterocolitis [8]. The functional significance of increased expression of the IL-2Rα receptor using purified γδ T cells in vitro was demonstrated.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Specifically, we found that γδ T cells were subtly activated, or primed, early in Salmonella serovar Typhimurium-infected calves, as evidenced by the increase in IL-2Rα on cells derived from intestinal lymphatic ducts. Minimal changes in γδ T cells were observed in the blood of infected calves, consistent with responses seen in human Salmonella serovar Typhimurium induced enterocolitis [8]. The functional significance of increased expression of the IL-2Rα receptor using purified γδ T cells in vitro was demonstrated.…”
Section: Discussionsupporting
confidence: 75%
“…Catheters were inserted into the mesenteric efferent lymphatic vessel following standard surgical procedures. Calves recovered from surgery for approximately 20 hours, then the time 0 lymphatic fluid and blood were collected just prior to infection with 4.7 × 10 7 to 4 × 10 8 CFUs of a natural calf isolate of Salmonella serovar Typhimurium (Type O, Group B) or mock infection with an equivalent volume of sterile Luria broth (LB) media. Prior to infection, 100 μl of Salmonella serovar Typhimurium stock was added to 5ml of LB media and shaken for 6 hours at 37°.…”
Section: Surgery and Experimental Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is reported that bacillus Calmette-Guérin vaccine application can exhibit significantly beneficial effect in controlling the malignancy, in particular the bladder cancers (41,42). Because many microbes are indicated to produce and secrete nonpeptide Ags for human ␥␦ T cells such as alkyl pyrophosphates and alkyl amines (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), it is tempting to speculate that these microbial nonpeptide Ags may contribute to the restriction of growth of incidental tumor cells via stimulation of ␥␦ T cells to proliferate and produce IFN-␥ as well as sensitization of the tumor cells for the ␥␦ T cell-mediated cytotoxicity. Our recent report suggested that ␥␦ T cells might provide innate immunity in patients with renal cell carcinomas, implicating a possible link between tumor immunity and urinary infections (56).…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of this subpopulation is not yet totally understood. However, the fact that their percentage dramatically increases in peripheral blood of patients infected by pathogens of viral, bacterial, or parasitic origin (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), suggest that these cells may be directly engaged in the response to infectious agents. A particular feature of these lymphocytes is that they are stimulated by nonpeptidic ligands in a major histocompatibility complex-unrestricted manner (24 -29).…”
mentioning
confidence: 99%